2007
DOI: 10.1254/jphs.sc0070155
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin, a Citrus Flavonoid That Improves Memory Impairment, Rescues Bulbectomy-Induced Cholinergic Neurodegeneration in Mice

Abstract: Abstract. We have recently reported that nobiletin, a citrus flavonoid, improves impaired memory in olfactory-bulbectomized (OBX) mice, which have been widely utilized as a useful paradigm that shares some major clinical features of Alzheimer's disease. Here, we examined the effects of nobiletin on OBX-induced cholinergic neurodegeneration in mice. OBX mice showed reduced acetylcholinesterase (AChE) staining and choline acetyltransferase (ChAT) expression in the hippocampus. An 11-day administration of nobilet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 14 publications
2
87
0
1
Order By: Relevance
“…On the other hand, there are a number of reports concerning a variety of biological effects of tangeretin and nobiletin, especially nobiletin, in addition to the concentrations of polymethoxy flavones in various species of citrus (10,11). For instances, direct and indirect evidences have been provided for anti-cancer effects (12)(13)(14)(15)(16)(17)(18)(19)(20), anti-inflammatory effects (21)(22)(23)(24), inhibition of NO production (25,26), enhancement of differentiation and lipolysis of adipocytes (27), prevention of cartilage destruction (28), improvement of memory impairment (29) and neurodegradation (30). However, no liver injury-suppressive effect of tangeretin and nobiletin has been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are a number of reports concerning a variety of biological effects of tangeretin and nobiletin, especially nobiletin, in addition to the concentrations of polymethoxy flavones in various species of citrus (10,11). For instances, direct and indirect evidences have been provided for anti-cancer effects (12)(13)(14)(15)(16)(17)(18)(19)(20), anti-inflammatory effects (21)(22)(23)(24), inhibition of NO production (25,26), enhancement of differentiation and lipolysis of adipocytes (27), prevention of cartilage destruction (28), improvement of memory impairment (29) and neurodegradation (30). However, no liver injury-suppressive effect of tangeretin and nobiletin has been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Galantamine exerts dual effects on the cholinergic system: inhibition of AChE and stimulation of postsynaptic nicotinic receptors [8]. Based on the efficacy of galantamine, screening studies have led to the identification and isolation of natural AChE inhibitors from herbs [9], plants [10], seeds and fruits [11]. In addition, recent studies have indicated that dietary polyunsaturated fatty acids (PUFAs) may be able to modulate cholinergic activity, either through enhancement of ACh release or inhibition of ACh hydrolysis (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…15,20) Moreover, our previous report showed that nobiletin ameliorates the NMDA receptor antagonist-induced learning impairment in association with ERK activation in mice. 18) This is the first report demonstrating that nobiletin significantly upregulated NR1, NR2A, and NR2B mRNA levels in PC12D cells (Fig. 2).…”
Section: Discussionmentioning
confidence: 51%
“…14) We previously identified nobiletin, a polymethoxylated flavone from Citrus depressa peels, as a natural compound with neurotrophic effects such as neurite outgrowth on PC12D cells, 15) which is a subclone of PC12 cells that is known as a model of neuronal differentiation cell system. Nobiletin improves learning and memory impairment in amyloid precursor protein transgenic mice, 16) chronically Aβ-infused AD model rats, 17) olfactory-bulbectomized mice, 18) and NMDA receptor antagonist MK-801-induced learning impaired mice. 19) Nobiletin prominently stimulates CRE-dependent transcription in PC12D cells 20) by activating the PKA/MEK/extracellular signal-regulated kinase (ERK)/CREB signaling pathway.…”
mentioning
confidence: 99%